Students’ Learning Motivation toward the Implementation of Blended Learning during Post-Pandemic EFL Classroom - Jibriil Ahmad Abdillah; Sueb Sueb (Faculty of Letters, Universitas Abdurachman Saleh Situbondo, 2022)
As the situation of the Covid-19 pandemic in Indonesia is gradually recovering, schools may reopen for limited face-to-face learning under particular measures during this transition period to the post-pandemic. This study aims to describe the implementation of blended learning and student motivation in secondary schools in limited face-to-face classes. This qualitative study collected the data through observation and questionnaires, involving two classes of junior high school students (N=70) of one urban public school in Sidoarjo, East Java, where blended learning was mandatory during the transition period. The results show a clear difference between the two modes; students who participated during the in-person learning session are more enthusiastic, engaged, and active during teaching and learning activities, while students who studied at home seemed quieter and less motivated to learn during the blended learning session. Students further considered blended learning as a way to increase their learning motivation. They were more interested in the subject and had an easier way to find material online. Furthermore, various types of activities such as group and pair work, collaborative learning, and individual learning can be used to increase students’ engagement and interests during communicative language practice. The extrinsic and intrinsic factors of students as learning drivers should be considered by the teacher before applying certain learning methods and learning approaches, especially for English learning after the pandemic.